2021
DOI: 10.7759/cureus.18647
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent Segment Disease (ASD) in Incidental Segmental Fused Vertebra and Comparison With the Effect of Stabilization Systems on ASD

Abstract: Adjacent segment disease is a controversial process after spine stabilization. The two important factors discussed are natural aging and hypermobility in incidental segmental fusion anomalies; patients have two or more fused vertebrae from birth, which are the results of spinal movement restriction due to the fusion of some spinal units. This article's main purpose is to determine the degree of relationship of hypermobility and the aging process in the deterioration of the disks adjacent to fusion. MethodsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Spinal fusion surgery accelerates the onset of ASD by increasing intervertebral mobility and mechanical stress, resulting in severe back pain, radicular symptoms, or neurogenic intermittent claudication, which can seriously affect people's daily lives [41][42][43]. It has been reported that the incidence of a second operation for ASD was Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal fusion surgery accelerates the onset of ASD by increasing intervertebral mobility and mechanical stress, resulting in severe back pain, radicular symptoms, or neurogenic intermittent claudication, which can seriously affect people's daily lives [41][42][43]. It has been reported that the incidence of a second operation for ASD was Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, advances in medical technology in recent years have helped promote the use of cortical bone trajectory (CBT) screws, which, compared with TT screws, cause only mild denudation of the soft tissue and less nerve and vascular damage and have a greater anti-pullout force [2]. However, due to the intraoperative resection of the lamina and intervertebral disc, injury of the facet joint and fusion of long segments, the range of motion (ROM) and stress of adjacent segments are increased, thus accelerating the degeneration of adjacent segments [3][4][5]. As a result, a series of resulting clinical symptoms affects the patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of normal mobility brought on by the stiff immobilization of the motion segment might trigger compensatory increases in the motion and intradiscal pressure of neighbouring segments. In turn, this quickens degeneration and raises the possibility of neighboring segment illness (Song et al, 2011;Hekimoglu et al, 2021). When compared to the normal models in our investigation, the postoperative models with normal bone quality showed comparable or even less mobility in the neighboring segments.…”
Section: Discussionmentioning
confidence: 53%